Mannheimia haemolytica Leukotoxin Activates a Nonreceptor Tyrosine Kinase Signaling Cascade in Bovine Leukocytes, Which Induces Biological Effects - Jeyaseelan, S. (American Society for Microbiology, 2001)
The leukotoxin (LktA) produced by Mannheimia haemolytica binds to bovine lymphocyte function-associated antigen 1 (LFA-1) and induces biological effects in bovine leukocytes in a cellular and species-specific fashion. We have previously shown that LktA also binds to porcine LFA-1 without eliciting any effects. These findings suggest that the specificity of LktA effects must entail both binding to LFA-1 and activation of signaling pathways which are present in bovine leukocytes. However, the signaling pathways leading to biological effects upon LktA binding to LFA-1 have not been characterized. In this context, several reports have indicated that ligand binding to LFA-1 results in activation of a nonreceptor tyrosine kinase (NRTK) signaling cascade. We designed experiments with the following objectives: (i) to determine whether LktA binding to LFA-1 leads to activation of NRTKs, (ii) to examine whether LktA-induced NRTK activation is target cell specific, and (iii) to determine whether LktA-induced NRTK activation is required for biological effects. We used a biologically inactive mutant leukotoxin (ΔLktA) for comparison with LktA. Our results indicate that LktA induces tyrosine phosphorylation (TP) of the CD18 tail of LFA-1 in bovine leukocytes. The ΔLktA mutant does not induce TP of the CD18 tail, albeit binding to bovine LFA-1. LktA-induced TP of the CD18 tail was attenuated by an NRTK inhibitor, herbimycin A; a phosphatidylinositol 3′-kinase (PI 3-kinase) inhibitor, wortmannin; and a Src kinase inhibitor, PP2, in a concentration-dependent manner. Furthermore, LktA induces TP of the CD18 tail in bovine, but not porcine, leukocytes. Moreover, LktA-induced intracellular calcium ([Ca(2+)](i)) elevation was also inhibited by herbimycin A, wortmannin, and PP2. Thus, our data represent the first evidence that binding of LktA to bovine LFA-1 induces a species-specific NRTK signaling cascade involving PI 3-kinase and Src kinases and that this signaling cascade is required for LktA-induced biological effects.